2012
DOI: 10.1111/j.1464-410x.2012.11198.x
|View full text |Cite
|
Sign up to set email alerts
|

A national study of adverse effects and global quality of life among candidates for curative treatment for prostate cancer

Abstract: What's known on the subject? and What does the study add?• Studies comparing adverse effects after different treatment methods are few and lack information on additional treatment and cancer relapse. Some US studies have provided population-based estimates on adverse effects, however, figures from Europe are most often based on mono-institutional experience or multicentre studies from high-volume university-affiliated hospitals with selected patient populations. Few studies have investigated the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 39 publications
4
51
0
Order By: Relevance
“…Hence, an increasing number of studies are turning their attention to the harms associated with PSA testing such as overdiagnosis and overtreatment [12,13,14,15], negative effects on the quality of life [16], harms related to subsequent evaluation and therapy [6,17,18] or the investigation of prognostic factors predicting survival in men with prostate cancer [19]. The European Prostate Centre Innsbruck (EPI) at the Department of Urology of Innsbruck Medical University Hospital with a wide experience of PSA testing is especially interested in patient-relevant outcomes after prostate cancer therapy, particularly after radical prostatectomy (RP).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an increasing number of studies are turning their attention to the harms associated with PSA testing such as overdiagnosis and overtreatment [12,13,14,15], negative effects on the quality of life [16], harms related to subsequent evaluation and therapy [6,17,18] or the investigation of prognostic factors predicting survival in men with prostate cancer [19]. The European Prostate Centre Innsbruck (EPI) at the Department of Urology of Innsbruck Medical University Hospital with a wide experience of PSA testing is especially interested in patient-relevant outcomes after prostate cancer therapy, particularly after radical prostatectomy (RP).…”
Section: Introductionmentioning
confidence: 99%
“…2 Voznesensky et al 1 cited one of several recent studies showing that return to baseline erectile function after radical pelvic surgery has been greatly overestimated. [2][3][4] However, they also underestimate rates of ED after pelvic radiation therapy 3,4 and among survivors of hematologic and childhood malignancies.…”
Section: Prevalence Of Sexual Problems In Men After Cancermentioning
confidence: 99%
“…In addition, the relationship between post--treatment problems and HRQOL was examined (8). However, despite increased focus on physical problems following those treatments, little attention has been given to related psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HRQOL measures are an important consideration for deciding treatment. Recently, a number of studies have reported HRQOL in cases of localized PCa with the aim of providing information concerning the potential consequences of treatments (6)(7)(8). However, despite increased focus on disease-specific HRQOL, less attention has been given to the psychological well-being of affected patients.…”
Section: Introductionmentioning
confidence: 99%